2000
DOI: 10.1046/j.1523-1755.2000.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil reduces myofibroblast infiltration and collagen III deposition in rat remnant kidney

Abstract: Reduction of interstitial myofibroblast infiltration may be an important event by which MMF significantly prevents renal injury following subtotal renal ablation. Thus, our results suggest that MMF could be useful to limit the progression of chronic renal disease toward end-stage renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 26 publications
7
103
0
3
Order By: Relevance
“…Whilst vimentin is not specific for fibroblastoid cells [72], staining of both vimentin and tubular β-catenin is currently being used clinically to assess early renal injury (clinical trial NCT#01079143) [73]. Although α-SMA represents the most commonly used marker in EMT, heterogeneity of expression means that this protein is not a definitive marker [74], and clarification of EMT in fibrosis should be regarded with caution, since confirmation of this phenotypic transformation appears to depend upon a complex interplay of events. The concept that cells of an epithelial origin are able to undergo a phenotypic transformation in response to pathophysiological stimuli and ultimately traverse the TBM has, up until recently, been universally accepted.…”
Section: Emt In the Kidneymentioning
confidence: 99%
“…Whilst vimentin is not specific for fibroblastoid cells [72], staining of both vimentin and tubular β-catenin is currently being used clinically to assess early renal injury (clinical trial NCT#01079143) [73]. Although α-SMA represents the most commonly used marker in EMT, heterogeneity of expression means that this protein is not a definitive marker [74], and clarification of EMT in fibrosis should be regarded with caution, since confirmation of this phenotypic transformation appears to depend upon a complex interplay of events. The concept that cells of an epithelial origin are able to undergo a phenotypic transformation in response to pathophysiological stimuli and ultimately traverse the TBM has, up until recently, been universally accepted.…”
Section: Emt In the Kidneymentioning
confidence: 99%
“…In addition, MMF appears to have a variety of anti-inflammatory actions that are independent of its effect on cell-mediated immunity. [7][8][9][10][11] Despite the successful induction of proliferative GN, relapses are common, ranging from 10 to 65%. [12,13] Continued renal damage can adversely affect long-term renal survival with each relapse, [14] and the treatment of these relapses is burdened by the toxicity.…”
Section: G M Sahin Et Almentioning
confidence: 99%
“…4 Its renoprotective action was related to reduced infiltration of inflammatory cells, but direct effects on resident cells, mainly interstitial myofibroblasts and mesangial cells, have also been suggested. 5,6 We and others have demonstrated that MPA inhibits mesangial proliferation and secretion of extracellular matrix proteins, 7,8 all effects that might contribute to the favorable effects of mycophenolate mofetil in chronic fibrotic kidney diseases. However, inhibition of mesangial activation caused by MPA treatment was accompanied by a strong and sustained increase in SMA expression, 8 which is usually associated with mesangial proliferation.…”
mentioning
confidence: 98%